Vertebral Lesions - Manfrè, Luigi (Springer International Publishing : Imprint: Springer, 2017)
This easy-to-consult guide describes new minimally invasive procedures for the treatment of vertebral lesions that are accompanied by fewer complications and side-effects, reduce the risks of anesthesia, and lower costs. Clear accounts are provided of CT and X-ray guided techniques for vertebral augmentation in different regions of the spine and for the treatment of vertebral tumors by means of cryoablation, radiofrequency ablation, and embolization. Helpful information is also provided on imaging, biomechanics, biopsy, and biomaterials. Like other books in the Springer series New Procedures in Spinal Interventional Neuroradiology, this practice-oriented volume will fill a significant gap in the literature and meet the need expressed by a large number of specialists (interventional neuroradiologists and radiologists, neurosurgeons, and orthopedists) for a topical and handy guide that specifically illustrates the presently available materials and methods.
Keywords: Medicine.; Interventional radiology.; Neurosurgery.; Orthopedics.; Minimally invasive surgery.; elektronické knihy; electronic books